The Influence Of Workplace Facilities And Service Quality On Community Satisfaction At The Suka Banjar Village Office, Tetap Subdistrict, Kaur Regency - Sari, Pitriya Anggun; Soleh, Ahmad; Abi, Yudi Irawan (Utami Publisher, 2025)
The purpose of this study is to determine the influence of workplace facilities and service quality on community satisfaction at the suka banjar village office, tetap subdistrict, kaur regency. the data collection method in this study used a questionnaire technique, with a sample of 1,000 respondents. the results of the study show that the multiple linear regression equation is y = 26.889 + 0.332 x1 + 0.125 x2 + 3.417. the coefficients are positive, indicating a direct relationship between the variables of workplace facilities (x1) and service quality (x2) and community satisfaction at the suka banjar village office, tetap subdistrict, kaur regency. the results indicate that the test for workplace facilities (X1) shows a t-count of 5.336 > t-table of 1.660 and a significance value of 0.000 < 0.05, thus the alternative hypothesis (ha) is accepted and the null hypothesis (ho) is rejected. this means that workplace facilities (X1) have a positive and significant influence on community satisfaction at the suka banjar village office, tetap subdistrict, kaur regency. the test for service quality (X2) shows a t-count of 2.026 > t-table of 1.660 and a significance value of 0.045 < 0.05, so the alternative hypothesis (ha) is accepted and the null hypothesis (ho) is rejected. this means that service quality (x2) has a positive and significant influence on community satisfaction at the suka banjar village office, tetap subdistrict, kaur regency.based on the comparison between the f-count and the f-table, the f-count value is greater than the f-table value, which is 17.314 > 2.70. therefore, it is concluded that the hypothesis is accepted, meaning there is a simultaneous influence between workplace facilities (X1) and service quality (X2) on community satisfaction at the suka banjar village office, tetap subdistrict, kaur regency. this is shown by the significance level of 0.000 < 0.05.